The Results of Archaeological Excavations in the Ancient Site of Ai-Khanum - Mojadidi, Abdul Jalil (Journal of Social Sciences - Kabul University, 2023)
The ancient site of Ai-Khanum is located at the intersection of Amu and Kokcheh rivers in northern Afghanistan. And during archaeological excavations, a Greek town was discovered in Ai-Khanum village, Takhar province, which was built during the time of Alexander Macedonian. And many ancient evidences including pottery, treasure of coins of Greco-Bactrian kings, inscriptions in Greek and Aramaic script, bronze and stone statues of Greek gods and famous people, precious stones such as lapis lazuli, turquoise and ruby ​​and hundreds of ancient artifacts. Other ruins of residential buildings, palaces, tombs, temples and sports fields have been found in this town, which stabilizes the Greco-Bactrian civilization in northern Afghanistan. In this article, the library method is used to explain the archaeological discoveries in the ancient site of Ai-Khanum. And the findings of the research show that the ancient site of Ai-Khanum was not built on any previous building or town, but the local arts of Bactria played an effective role in the beauty and evolution of Greek arts.